2023
DOI: 10.1002/jcsm.13220
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for inefficient contraction and abnormal mitochondrial activity in sarcopenia using magnetic resonance spectroscopy

Abstract: Background Mitochondrial dysfunction has been implicated in sarcopenia. 31 P magnetic resonance spectroscopy (MRS) enables non-invasive measurement of adenosine triphosphate (ATP) synthesis rates to probe mitochondrial function. Here, we assessed muscle energetics in older sarcopenic and non-sarcopenic men and compared with muscle biopsy-derived markers of mitochondrial function. Methods Twenty Chinese men with sarcopenia (SARC, age = 73.1 ± 4.1 years) and 19 healthy aged and sex-matched controls (CON, age = 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…At present, the exact pathogenesis of sarcopenia remains unclear. Nevertheless, some studies have found abnormalities in the morphology of the neuromuscular junction (NMJ) (Carnio et al., 2014 ; Iyer et al., 2021 ; Shi et al., 2014 ; Sirago et al., 2023 ) and changes in mitochondrial function (Baraldo et al., 2020 ; Dupuis et al., 2009 ; Spendiff et al., 2016 ; Stephenson et al., 2023 ; Xiao et al., 2020 ) in individuals with sarcopenia. These findings suggest that impairments in the NMJs and mitochondrial function could be potential contributing factors to the development of sarcopenia (Ahn et al., 2019 ; Jang et al., 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…At present, the exact pathogenesis of sarcopenia remains unclear. Nevertheless, some studies have found abnormalities in the morphology of the neuromuscular junction (NMJ) (Carnio et al., 2014 ; Iyer et al., 2021 ; Shi et al., 2014 ; Sirago et al., 2023 ) and changes in mitochondrial function (Baraldo et al., 2020 ; Dupuis et al., 2009 ; Spendiff et al., 2016 ; Stephenson et al., 2023 ; Xiao et al., 2020 ) in individuals with sarcopenia. These findings suggest that impairments in the NMJs and mitochondrial function could be potential contributing factors to the development of sarcopenia (Ahn et al., 2019 ; Jang et al., 2010 ).…”
Section: Introductionmentioning
confidence: 99%